2017
DOI: 10.5312/wjo.v8.i6.484
|View full text |Cite
|
Sign up to set email alerts
|

Medial tibial plateau morphology and stress fracture location: A magnetic resonance imaging study

Abstract: AIMTo determine the location of medial tibial plateau stress fractures and its relationship with tibial plateau morphology using magnetic resonance imaging (MRI).METHODSA retrospective review of patients with a diagnosis of stress fracture of the medial tibial plateau was performed for a 5-year period. Fourteen patients [three female and 11 male, with an average age of 36.4 years (range, 15-50 years)], who underwent knee MRI, were included. The appearance of the tibial plateau stress fracture and the geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
9
0
6
Order By: Relevance
“…Other factors such as surgery for anterior cruciate ligament reconstruction (14) and unicompartmental knee arthroplasty (15,16), drug-induced osteoporosis (17,18), and even primary and postpartum osteoporosis without BP use (19,20) can also cause these fractures. Generally, medial tibial plateau stress fractures can be managed conservatively simply by the cessation of sports activity, and symptoms usually resolve within two months (12,13,21). We treated this patient with a lateral wedge insole and protective weight-bearing with a T-cane, but this case had a concomitant lateral tibial plateau fracture, and further resulted in a delayed healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors such as surgery for anterior cruciate ligament reconstruction (14) and unicompartmental knee arthroplasty (15,16), drug-induced osteoporosis (17,18), and even primary and postpartum osteoporosis without BP use (19,20) can also cause these fractures. Generally, medial tibial plateau stress fractures can be managed conservatively simply by the cessation of sports activity, and symptoms usually resolve within two months (12,13,21). We treated this patient with a lateral wedge insole and protective weight-bearing with a T-cane, but this case had a concomitant lateral tibial plateau fracture, and further resulted in a delayed healing.…”
Section: Discussionmentioning
confidence: 99%
“…In such a BP-related atypical insufficiency fracture, early short-term casting and / or knee supporter might be considered to prevent delayed union and deformity of the fracture site. In addition, MRI-STIR images are the most useful investigative tool when the index of suspicion is high (21,22). Since X-ray changes are quite subtle during the period of prodromal pain, we recommend using MRI to investigate patients treated long-term with BP.…”
Section: Discussionmentioning
confidence: 99%
“…A tíbia é o osso mais afetado por fraturas por estresse, especialmente em corredores de longa distância. A diáfise da tíbia é o local mais comum, enquanto as lesões na metáfise proximal da tíbia são raras (1)(2)(3) . Estudos descrevem alta incidência de bilateralidade nas fraturas por estresse da tíbia proximal (6)(7) .…”
Section: Discussionunclassified
“…Essa lesão pode ser facilmente confundida com outros diagnósticos diferencias, justamente porque o local de dor e sensibilidade a palpação é muito semelhante a lesões meniscais e tendinite da pata de ganso, que são lesões comuns em pacientes corredores. A suspeita clínica é essencial para o diagnóstico correto (1)(2)(3) .…”
Section: Introductionunclassified
“…In addition, studies [ 34 ] have shown that the bone mineral density of the medial tibial plateau is lower than that of the lateral side, which is one of the reasons that the medial side is more vulnerable. Yukata et al [ 35 ] studied stress fractures of the tibial plateau and found that all stress fractures occurred in the medial plateau and that the fracture location was related to the posterior tilt of the medial tibial plateau. In our study, we found that in the knee longitudinal collision injury test, a longitudinal low-speed impact often led to an inner knee injury and a high-speed collision often resulted in both medial and lateral knee injuries.…”
Section: Discussionmentioning
confidence: 99%